Risk Analysis In Indonesian Educational Online Learning Systems: A Systematic Literature Review - Sama, Hendi; Tjahyadi, Surya; Titoni, Erica (Universitas Medan Area, 2025)
Over the past few years, the idea of online learning has gained popularity and due to the COVID-19 pandemic, has become essential everywhere, including in Indonesia. Nevertheless, the deployment of e-learning management systems has brought about several IT hazards that affect academic operations' user experience security and overall operational efficacy worldwide. This study uses a systematic literature review (SLR) of research publications indexed in Google Scholar to examine the possible dangers related to e-learning management systems in academic institutions. The classification, assessment, and identification of the hazards that educational institutions encounter while incorporating e-learning systems into their infrastructure are the main objectives of this study. Issues like operational failures, obsolete hardware and software, cybersecurity threats, network accessibility and stability concerns, data privacy, and illegal access are the main topics of this study. Additionally, this study highlights the necessity of more effective and focused risk mitigation techniques created especially to meet the demands of Indonesian academic settings